Analysis of Beneficiaries Satisfaction Measurement at Baznas Scholarship Institution - Fadhil, Muhammad (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
The service of the Organization must be excellent to give satisfaction to beneficiaries. The National Board of Zakat (BAZNAS) through the BAZNAS Scholarship Institution (LBB) have a program to give a scholarship for Indonesian student in Indonesia, Malaysia, Egypt, and India. To support this program, LBB must have good scholarship management and communication. This study aims to identify satisfaction of communication service and scholarship management from BAZNAS Scholarship Beneficiaries using analysis of reliability, Top-Two Box method, and correlation test using SPSS application for data processing. The data was collected through an online questionnaire. A total of 321 were the research samples. The results of Cronbach's Alpha test on the questionnaires and data show that the data are reliable in this study (Cronbach's Alpha value = 0.922). Through the analysis using the Top-Two Box method, prove that LBB has good satisfaction from beneficiaries. The overall value of participant’s satisfaction is 98.18% was the satisfaction of communication service higher than scholarship management. The highest score of satisfaction item is language ability and the lowest score is the punctuality of scholarship distribution. In this research, we analyze the correlation of gender, age, and level of education with the results are 0.525; 0.401; and 0.927. With the high satisfaction results, we hope our Beneficiaries can be a loyal Muzakki in the future.